PENGARUH TERPAAN PEMASARAN SOSIAL PENCEGAHAN STUNTING DAN TINGKAT PENDIDIKAN MASYARAKAT DAN TINGKAT PENDIDIKAN MASYARAKAT TERHADAP PERILAKU MASYARAKAT DALAM UPAYA PENCEGAHAN STUNTING - Nadia Hutaminingtyas; Joyo Nur Suryanto Gono; Tandiyo Pradekso (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Children’s growth has been a concern for every parent. As of 2021, there are various kinds of health problems in children one of which is stunting. The national stunting prevalence rate as of 2021 is at 24 percent. This is above the threshold set by WHO, namely 20 percent. This problem is of concern to both the governments, the private sector, and all parents who have children. This research is a quantitative research with explanatory methods. By distributing questionnaires to 100 respondents with the characteristics of parents who have children under 6 years of age, have received information about stunting, and have had their children checked at Posyandu in Tegal City, the results showed that social marketing exposure to stunting prevention had a positive influence on stunting prevention behavior. This is reinforced by a significance value of 0.00 and a coefficient of determination value of 0.860. These findings are in line with the Integrated Theory of Health Behavior Change used. Apart from that, the level of education also has a positive influence on stunting prevention behavior. This is proven by a significance value of 0.00 and a coefficient of determination value of 0.863. The results of the research that has been carried out are in line with the Social Categorization Theory used.